Living life coming and going: migratory cycles of Argentine forestry workers - Albertí, Alfonsina Verónica (2018)
This article deals with forestry workers from the province of Misiones (northeast Argentina) who migrate to find temporary employment in other provinces. Our objective is to understand the link between spatial mobility and access to employment. Based on a qualitative methodology, we reconstruct the annual migratory cycles of workers, taking into account the variety of spatial paths and temporalities involved in migration and analyzing how these characteristics vary according to each worker’s attributes, household strategies, and networks of access to employment.